Modular Assembly of Cell-targeting Devices Based on an Uncommon G-quadruplex Aptamer - Felipe Opazo; Laura Eiden; Line Hansen; Falk Rohrbach; Jesper Wengel; Jørgen Kjems; Günter Mayer (Molecular Therapy: Nucleic Acids, 2015)
Aptamers are valuable tools that provide great potential to develop cost-effective diagnostics and therapies in the biomedical field. Here, we report a novel DNA aptamer that folds into an unconventional G-quadruplex structure able to recognize and enter specifically into human Burkitt's lymphoma cells. We further optimized this aptamer to a highly versatile and stable minimized version. The minimized aptamer can be easily equipped with different functionalities like quantum dots, organic dyes, or even a second different aptamer domain yielding a bi-paratopic aptamer. Although the target molecule of the aptamer remains unknown, our microscopy and pharmacological studies revealed that the aptamer hijacks the clathrin-mediated endocytosis pathway for its cellular internalization. We conclude that this novel class of aptamers can be used as a modular tool to specifically deliver different cargoes into malignant cells. This work provides a thorough characterization of the aptamer and we expect that our strategy will pave the path for future therapeutic applications.